Chitosan nanoparticle-based system: a new insight into the promising controlled release system for lung cancer treatment - Cha, Yee Kuen; Masarudin, Mas Jaffri (Multidisciplinary Digital Publishing Institute, 2021)
Lung cancer has been recognized as one of the most often diagnosed and perhaps most lethal cancer diseases worldwide. Conventional chemotherapy for lung cancer-related diseases has bumped into various limitations and challenges, including non-targeted drug delivery, short drug retention period, low therapeutic efficacy, and multidrug resistance (MDR). Chitosan (CS), a natural polymer derived from deacetylation of chitin, and comprised of arbitrarily distributed β-(1-4)-linked d-glucosamine (deacetylated unit) and N-acetyl-d-glucosamine (acetylated unit) that exhibits magnificent characteristics, including being mucoadhesive, biodegradable, and biocompatible, has emerged as an essential element for the development of a nano-particulate delivery vehicle. Additionally, the flexibility of CS structure due to the free protonable amino groups in the CS backbone has made it easy for the modification and functionalization of CS to be developed into a nanoparticle system with high adaptability in lung cancer treatment. In this review, the current state of chitosan nanoparticle (CNP) systems, including the advantages, challenges, and opportunities, will be discussed, followed by drug release mechanisms and mathematical kinetic models. Subsequently, various modification routes of CNP for improved and enhanced therapeutic efficacy, as well as other restrictions of conventional drug administration for lung cancer treatment, are covered.